Pengaruh Tingkat Stres terhadap Kebiasaan Meminum Alkohol pada Remaja dan Dewasa: Kajian Pustaka - Shahnaz Salsabilla Putri; Nuzirwan Acang; Tryando Bhatara (UNISBA Press, 2022)
Abstract. Stress is the body's response to the demands of a non-specific one. In dealing with stress one can also use the way of coping stress that is divided into two, there is emotional stress coping for example individuals cope with emotions when stressed, and there are coping stress problems where individuals tend to want to find the cause of stress appears and then solves it. Aspects of coping strategies of Emotion – focused coping include acceptance, something full of stress is a situation that forces him to overcome the problem, which allows the individual to find a way to handle it. Where you can use alcoholic beverages. Stress can trigger teenagers or adults to consume alcoholic beverages because when stressed a person's body will release the hormone cortisol, when drinking alcohol then alcohol will be a depressant for the central nervous system, so that when drinking alcohol teenagers and adults can feel a momentary loss of stress. The writing of this article is a literature study that aims to provide information about the influence of a person's stress levels on his drinking habits. Abstrak. Stress merupakan respon dari tubuh terhadap tuntutan dari yang non spesifik. dalam menghadapi stres seseorang juga dapat menggunakan cara coping stress yang dibagi menjadi dua, ada coping stress emosi contohnya individu mengatasi emosinya ketika stres, dan ada coping stress problem dimana individu cenderung ingin mencari penyebab stresnya muncul lalu menyelesaikannya. Aspek aspek strategi coping dari Emotion – focused coping antara lain ada berupa Penerimaan, sesuatu yang penuh dengan stres merupakan suatu keadaan yang memaksanya untuk mengatasi masalah tersebut, yang memungkinkan individu mencari cara untuk menanganinya. Dimana bisa menggunakan minuman beralkohol. Stres bisa memicu remaja ataupun orang dewasa mengonsumsi minuman alkohol karena saat stres tubuh seseorang akan melepaskan hormon kortisol, ketika meminum alkohol maka alkohol akan menjadi depresan untuk sistem saraf pusat, sehingga ketika meminum alkohol remaja dan dewasa dapat merasakan hilangnya stres secara sesaat. Penulisan artikel ini merupakan suatu kajian pustaka yang bertujuan untuk memberikan informasi tentang pengaruh dari tingkat stres seseorang terhadap kebiasaan meminum alkoholnya.